Emotion recognition and processing in patients with mild cognitive impairment: A systematic review - Morellini, Lucia; Izzo, Alessia; Rossi, Stefania; Zerboni, Giorgia; Rege-Colet, Laura; Ceroni, Martino; Biglia, Elena; Sacco, Leonardo (Frontiers in Psychology, 2022)
The purpose of the present review was to investigate emotion recognition and processing in patients with mild cognitive impairment (MCI) in order to update the state of current literature on this important but undervalued topic. We especially identified 15 papers published between 2012 and 2022 which meet inclusion criteria. Papers search, selection, and extraction followed the PRISMA guidelines. We used a narrative synthesis approach in order to report a summary of the main findings taken from all papers. Results collected are still ambiguous: some studies did not find any differences between MCI and Healthy Controls (HC) groups in emotion recognition and processing, and other results reported emotion-specific deficits in emotion recognition regarding MCI patients (both regarding negative and neutral emotions). It’s essential to underline that these findings could not be generalized to the whole MCI population, due to the heterogeneous use of measures and composition of the sample. This does not allow us to make a comprehensive comparison between the results: our suggestion for future research is to align the results using the same type of tests and emotion recognition assessment.